Elevated liver fibrosis index FIB-4 is not reliable for HCC risk stratification in predominantly non-Asian CHB patients. Issue 38 (September 2016) - Demir, Münevver; Grünewald, Friederike; Lang, Sonja; Schramm, Christoph; Bowe, Andrea; Mück, Vera; Kütting, Fabian; Goeser, Tobias; Steffen, Hans-Michael
Abstract : Abstract: We aimed to validate the liver fibrosis index FIB-4 as a model for risk stratification of hepatocellular carcinoma development in predominantly non-Asian patients with chronic hepatitis B infection seen at a tertiary referral center in Germany. We retrospectively analyzed 373 adult patients with chronic hepatitis B infection. Patient demographics, hepatitis B markers, antiviral treatment, laboratory parameters, results from liver imaging and histology were recorded. Patients were divided into 2 groups according to their FIB-4 levels and their hazard ratios for developing hepatocellular carcinoma were analyzed adjusted for age, sex, body mass index, alcohol consumption, and antiviral medication. Median follow-up was 8.7 years (range 1–21.3 years), 93% of patients were of non-Asian origin, and 64% were male. Compared with patients with a low FIB-4 (<1.25) patients with FIB-4 ≥1.25 showed a hazard ratio for incidence of hepatocellular carcinoma of 3.03 (95% confidence interval (CI): 1.24–7.41) and an adjusted hazard ratio of 1.75 (95% CI: 0.64–4.74). Notably, 68% of patients with liver cirrhosis and 68% of those who developed HCC during observation had a low FIB-4 (<1.25). We could not confirm that a FIB-4 value ≥1.25 is a reliable clinical indicator for incidence of hepatocellular carcinoma in predominantly non-Asian patients with chronic hepatitis B. Further studies in geographically and ethnically diverse populations are needed to prove its utility as a predictive tool. Abstract : Supplemental Digital Content is available in the text